Juvenile Delinquent Behavior Among In-School Adolescents: Examining The Roles Of Peer Influence And Gender - Uye, Olubunmi O. James, Emmanuel E.; Ojo, Adeshina A. (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the contributions of peer influence and gender on juvenile delinquent behavior among in-school adolescents. Cross-sectional survey design was employed while purposive sampling technique was utilized to select Egor Local Government Area, Edo state. Data were conveniently collected from 218 participants using validated questionnaires and analyzed with independent samples t-test and the hypotheses accepted at p <.01 level of significance. The result revealed that peer influence significantly contributed to juvenile delinquent behavior among study participants, t(218) = -10.53, p <.01 such that those high on peer influence (M=71.98, S.D= 29.66) reported significantly higher scores on juvenile delinquent behavior compared to their counterparts who scored low on peer influence (M = 35.12, S.D =17.79). Furthermore, the result confirmed that gender significantly influenced juvenile delinquent behavior among study participants, t (218) = -12.28, p <.01 such that male participants reported higher scores on juvenile delinquent behavior (M =73.36, SD = 27.49) more than their female counterparts (M=32.71, SD =17.82). The study concludes that peer influence and gender significantly determined the involvement of study participants in juvenile delinquent behavior. The study recommends that parents and educational institutions should sensitize adolescents on the menace of being involved in delinquent behaviors that would likely affect their lives in the future